2013
DOI: 10.1037/a0032714
|View full text |Cite
|
Sign up to set email alerts
|

Stimulus fear-relevance and the vicarious learning pathway to childhood fears.

Abstract: Enhanced fear learning for fear-relevant stimuli has been demonstrated in procedures with adults in the laboratory. Three experiments investigated the effect of stimulus fear-relevance on vicarious fear learning in children (aged 6-11 years). Pictures of stimuli with different levels of fear-relevance (flowers, caterpillars, snakes, worms, and Australian marsupials) were presented alone or together with scared faces. In line with previous studies, children's fear beliefs and avoidance preferences increased for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

7
31
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
4
3

Relationship

3
4

Authors

Journals

citations
Cited by 24 publications
(38 citation statements)
references
References 49 publications
7
31
0
Order By: Relevance
“…The key findings were that results (a) replicated previous findings showing that fear-related vicarious learning leads to increases in children's fear beliefs and avoidance preferences (e.g., Askew et al, 2013;Reynolds et al, 2014), as well as demonstrating that compared to a control animal, children showed higher behavioral avoidance (e.g., Askew & Field, 2007;Dubi et al, 2008;Gerull & Rapee, 2002), heart rate, and attentional bias for fear-paired animals (Reynolds et al, 2014); (b) confirmed Dunne and Askew (2013) findings indicating that counterconditioning is successful in returning children's learned avoidance preferences to baseline levels; (c) for the first time demonstrated lower heart rate responses for fear-paired animals in a group receiving vicarious fear learning then positive modeling compared to a control group receiving vicarious fear learning only; and (d) showed that fear responses following vicarious fear-learning and then CS-only presentations were comparable to a control group receiving vicarious fear-learning only. Thus there was little evidence of extinction.…”
Section: Discussionsupporting
confidence: 79%
See 2 more Smart Citations
“…The key findings were that results (a) replicated previous findings showing that fear-related vicarious learning leads to increases in children's fear beliefs and avoidance preferences (e.g., Askew et al, 2013;Reynolds et al, 2014), as well as demonstrating that compared to a control animal, children showed higher behavioral avoidance (e.g., Askew & Field, 2007;Dubi et al, 2008;Gerull & Rapee, 2002), heart rate, and attentional bias for fear-paired animals (Reynolds et al, 2014); (b) confirmed Dunne and Askew (2013) findings indicating that counterconditioning is successful in returning children's learned avoidance preferences to baseline levels; (c) for the first time demonstrated lower heart rate responses for fear-paired animals in a group receiving vicarious fear learning then positive modeling compared to a control group receiving vicarious fear learning only; and (d) showed that fear responses following vicarious fear-learning and then CS-only presentations were comparable to a control group receiving vicarious fear-learning only. Thus there was little evidence of extinction.…”
Section: Discussionsupporting
confidence: 79%
“…The automated procedure then began with the first FBQ followed immediately by the vicarious learning procedure. Consistent with previous experiments (e.g., Askew et al, 2013;Askew & Field, 2007;Reynolds et al, 2014Reynolds et al, , 2015, during vicarious learning all children were presented with a slideshow on the monitor of 20 CS-US pairing trials: 10 animal-face trials (fear-paired CSs) and 10 animal-alone trials (unpaired CSs). In each pairing, the animal appeared first on the left-hand side of the screen for 1 s and remained on the screen when the picture of the face appeared on the right-hand side of the screen.…”
Section: Methodssupporting
confidence: 50%
See 1 more Smart Citation
“…It makes sense from an evolutionary perspective that only fear-relevant stimuli pose a threat to the survival of monkeys and thus vicarious learning would only occur for these fear-relevant stimuli, and this has received wide support (e.g. Mineka & Öhman, 2002; however, see also Askew et al, 2013).…”
mentioning
confidence: 99%
“…Subsequently, robust vicarious fear learning effects have been widely documented in children (e.g. Askew, Dunne, Özdil, Reynolds, & Field, 2013;Askew & Field, 2007;Askew, Kessock-Philip, & Field, 2008;Reynolds, Field, & Askew, 2014).…”
mentioning
confidence: 99%